Pengaruh Kepemimpinan Dan Motivasi Terhadap Kinerja Perangkat Desa Di Kecamatan Subah Kabupaten Batang - Sandra Wilhelmina Wijaya; Pandji Anoraga (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2021)
Performance is the result of performing a task or job in accordance with the authority and responsibility within an organization. The purpose of this study was to analyze the influence of leadership and motivation on the performance of village officials in Subah District, Batang Regency. A total of 122 village officials were taken as samples by accidental sampling. Multiple linear regression has been used to analyze the data in this study. The results showed that leadership and motivation had a positive and significant effect on the performance of village officials in Subah subdistrict, Batang district. Motivation is the variable that has the greatest influence on the performance of the Village apparatus. This shows that it is necessary to increase work motivation so that the performance of the Village apparatus in Subah District increases so that it is hoped that all Village apparatus in Subah District, Batang Regency can carry out their duties properly in accordance with the responsibilities given and organizational goals can be achieved properly